Retaining top talent: an introduction to the midlife review. Issue 5 (1st July 2020) - Butler, Steve
Abstract : Purpose: This paper aims to explore the emerging HR practice of midlife reviews which are being implemented as the mechanism to stimulate a conversation between employers and employees about next steps, second careers and flexible career solutions. Design/methodology/approach: This paper considers the approaches taken by Legal & General and AVIVA to implementing a midlife review programme within their organisation by interviews with senior managers involved in the implementation. Findings: A midlife review helps employees plan the important second phase of their career and enables employers to work with them to decide how they can best be supported. The midlife review includes deciding what kind of training or upskilling they might need, considering any changes to working patterns and tailoring the benefits package to suit older workers. Originality/value: The midlife review was introduced by the National Institute of Adult Continuing Education in 2015 and is only just starting to gain traction as a HR practice to retain older talent within an organisation. This paper attempts to raise awareness for the purpose of future research.